Modelling the quasi-static flexural behaviour of composite sandwich structures with uniform- and graded-density foam cores. (January 2022) - Liu, Haibao; Liu, Jun; Kaboglu, Cihan; Zhou, Jin; Kong, Xiangshao; Li, Shipeng; Blackman, Bamber R.K.; Kinloch, Anthony J.; Dear, John P.
Highlights: A three-dimensional FEA model is developed to predict the flexural behaviour of sandwich structures. This high-fidelity FEA simulation combines an elastic–plastic (E-P) damage model of the composite skins together with a crushable foam-core damage model. The crushable foam model is used to predict the mechanical response of the crushed foam core and subsequent ductile and shear fracture of the foam. Results from the modelling studies are compared with experimental results obtained from the sandwich structures manufactured with both uniform- and graded-density foam cores. Abstract: In-service, composite sandwich structures, which consist of fibre-composite skins (also termed face-sheets) adhesively bonded to a polymeric foam core, can encounter extreme quasi-static flexural loading that may cause serious damage to the sandwich structure. The ability to model the flexural behaviour of such structures can lead to improved designs and more efficient maintenance procedures. In the present research, a three-dimensional finite-element analysis (FEA) model is developed to predict the flexural behaviour of such sandwich structures using a commercial software package (i.e. Abaqus/Explicit). The high-fidelity FEA simulation combines an elastic–plastic (E-P) damage model of the composite skins together with a crushable foam-core damage model. The E-P damage model is implemented with a user subroutine to capture the damage, such as plastic deformation of the matrix and matrix cracking, fibre fracture and delamination cracking of the composite skins. The crushable foam model is used to predict (a) the mechanical response of the crushed foam core, (b) the induced damage from ductile fracture due to growth, coalescence and fracture of the cells and (c) the induced damage from shear fracture of the foam due to plastic shear-band localisation. Results from the modelling studies, such as the loading response and the damage mechanisms, are discussed and compared with the experimental results obtained from the sandwich structures manufactured with both uniform- and graded-density foam cores but which all have the same average core density. Good agreement is achieved between the experimental results and the predictions from the numerical modelling simulations.